SMART ANTENNA ARRAY PATTERNS SYNTHESIS: NULL STEERING AND MULTI-USER BEAMFORMING BY PHASE CONTROL - Mouhamadou, Moctar; Vaudon, Patrick; Rammal, Mohammed (Electromagnetic waves (Cambridge, Mass.), 2006)
In this article, an efficient method for the pattern synthesis of the linear antenna arrays with the prescribed null and multi-lobe Beamforming is presented. Multi-lobe pattern and adaptive nulling of the pattern is achieved by controlling only the phase of each array element. The proposed method is based on the Sequential Quadratic Programming (SQP) algorithm and the linear antenna array synthesis was modelled as a multi-ob jective optimization problem. Multi-ob jective optimization is concerned with the maximization (or minimization) of a vector of ob jectives functions in the directions of desired signal that can be sub ject of a number of constraints (in our case, the constraints can be imposed as the null in the direction of interfering signal). To verify the validity of the technique, several illustrative examples of uniform excited array patterns with the main beam is placed in the direction of the useful signal and null is placed in the direction of potential interferers, and multi-beam patterns are demonstrated.